Incremental large and small muscle mass exercise in patients with heart failure: evidence of preserved peripheral haemodynamics and metabolism - Esposito, F. (Acta Physiol (Oxf), 2014)
AIM: Doubt still remains as to whether peripheral vascular and skeletal muscle dysfunction accompanies the compromised cardiac function associated with heart failure with reduced ejection fraction (HFrEF). The aim of this study was to examine the effect of HFrEF on the haemodynamic and metabolic responses to exercise with both a large (cycle) and a small [knee extensor (KE)] muscle mass in comparison with well-matched healthy controls (Ctrls). METHODS: Utilizing blood sampling and thermodilution blood flow measurements, we studied incremental cycle and KE exercise in 12 patients with HFrEF (ejection fraction: 25 ± 3%) and eight Ctrls. RESULTS: Incremental cycle exercise in both groups [heart failure with reduced ejection fraction (HFrEF): 23 ± 1 to 116 ± 10; Ctrls: 22 ± 1 to 137 ± 5 W] resulted in a similar rise in blood flow (HFrEF: 1525 ± 132 to 4216 ± 408; Ctrls: 1774 ± 161 to 4713 ± 448 mL min(−1)), oxygen uptake (HFrEF: 206 ± 24 to 586 ± 34; Ctrls: 252 ± 21 to 747 ± 89 mL min(−1)) and lactate efflux across the leg (HFrEF: 479 ± 122 to 4929 ± 1255; Ctrls: 537 ± 155 to 5776 ± 1010 mM min(−1)). Vascular resistance fell similarly in both groups with increasing exercise intensity (HFrEF: 66 ± 10 to 24 ± 3; Ctrls: 69 ± 12 to 24 ± 4 mmHg L(−1) min(−1)). Incremental KE exercise also revealed similar haemodynamic and metabolic responses in both Ctrls and patients. CONCLUSION: Although assessed in a relatively small cohort, these data reveal that, when compared with well-matched healthy Ctrls, alterations in peripheral haemodynamics and skeletal muscle metabolism during exercise may not be an obligatory accompaniment to HFrEF.